State Recognition of Indigenous Peoples’ Territorial Rights under International Human Rights Law: A Comparative Study of Indonesia and Russia - Kharisma Gemilang; Sulistiyandari Sulistiyandari; Kartono Kartono; Sri Wahyu Handayani; Athari Farhani (Lampung Journal of International Law, 2025)
This study analyzes the recognition and protection of indigenous peoples’ territorial rights in Indonesia and Russia within the framework of international human rights law and identifies factors affecting their effectiveness. Using a normative legal method with conceptual and comparative approaches, the study finds that Indonesia has a relatively progressive framework through constitutional recognition of indigenous communities, yet implementation remains weak due to fragmented sectoral regulations and reliance on regional administrative recognition. Russia, by contrast, adopts a centralized model that recognizes only small-numbered indigenous peoples and limits collective ownership and meaningful participation. Both countries face tensions between state sovereignty over natural resources and international obligations to protect indigenous collective rights. The study recommends adopting a multi-level governance model that balances national interests and indigenous autonomy, alongside legal reforms to strengthen implementation of the Free, Prior, and Informed Consent (FPIC) principle, enabling more effective integration of international human rights norms into domestic legal systems..